Shared Soundscapes. Everyday Archiving and the Collaborative (Re)activation of Anthropological Collections - (:unkn) unknown (Routledge, 2024)
This contribution argues that “everyday archiving” is quintessential for the current collaborative (re)activation of historical sound recordings and images of oratory, music, and dance created by the local communities in two Peruvian regions. Local p...
Keywords: Paisajes sonoros; Archivos antropológicos